Digital image analysis to estimate the minimum number of Eurytrema coelomaticum eggs in the uterus of adult specimens - da Silva F. A.; Monteiro da Silva C.; de Almeida F. B.; Rodrigues-Silva R. (Helminthologia, 2018)
This study was carried out to estimate the minimal number of eggs present in adult E. coelomaticum uterus. Samples were collected during post-mortem inspection and were submitted to light microscopy (bright field). The length, width, the total area of the parasite, uterus, and eggs were measured. The ImageJ software was used to calculate the area of the different parameters analyzed in this study. It was possible to observe that the uterus corresponds on average to 51.9 % of the total area of the parasite (ranging from 45 to 64 %). The number of eggs present in the uterus of parasites ranged from 5,946 to 15,813. To estimate the number of eggs three scenarios were considered, where the first taken into account the number of whole eggs observed in the image. In the second way to estimate the number of eggs, all the structures were considered (whole eggs and fractions that could be delimited) and compared with manual counting. Finally, in the last scenario, was considered an occupancy rate of 100 % of the uterine area per eggs, since there are overlapping eggs and these cannot be correctly delimited and accounted for. This study describes an important tool for quantifying eggs in a nondestructive manner and aggregate information until then is not explained by other works.